Dynamic Cluster Based Routing Protocol with Sink Mobility Support for Underwater Wireless Sensor Networks - S, Anandalatchoumy; G, Sivaradje (International Journal of Engineering and Technology, 2018)
Underwater wireless sensor networks are energy resource constrained due to the scarce battery capacity. Energy efficient routing protocol is highly demanded to be developed for such networks. It is indeed a challenging task to design routing protocol that can achieve energy efficiency due to the dynamic and harsh underwater environment. A dynamic cluster based routing protocol coupled with sink mobility support (DCMMS) is proposed. Two schemes are combined together in the protocol. One is the formation of  clusters and two is the mobile sink management. The cluster formation includes cluster head election process and member           association process. Each cluster member sends the sensed data to the cluster head. Multiple mobile sinks are deployed to gather data directly from cluster heads. Finally, mobile sinks send the collected data after proper aggregation to the static sinks located at the surface. Thus, sink mobility and the dynamic clustering technique together help to balance the load among the nodes thereby       minimizing energy consumption to a significant extent and extending the network life span. Analytical simulations are extensively carried out to attest how the proposed protocol (DCMMS) achieves better performance with minimum energy consumption, less end to end delay and higher packet delivery ratio than its counterpart existing protocol (AA-RP).